Experimental quantum fingerprinting with weak coherent pulses - Xu F. (2015)
This work was supported in part by ID Quantique, CFI, OIT, NSERC RTI, the NSERC SPG FREQUENCY, the NSERC Discovery Program, the CRC Program, Connaught Innovation fund and Industry Canada. We thank A. Ignjatovic, Pedro Palacios-Avila, Z. Tang and Francisco de Zela for valuable discussions. Particularly, F. Xu and K. Wei thank V. Makarov for his hospitality during their visit to IQC. We acknowledge the support from the Mike and Ophelia Lazaridis Fellowship, the Office of Naval Research (ONR), the Air Force Office of Scientific Research (AFOSR), the National Natural Science Foundation of China (Grant No. 61178010), China Scholarship Council (No. 201406470051), the University of Hong Kong Physics Department Summer Overseas Research Program and the Science Faculty Overseas Research Fellowship, CONCYTEC-Peru, USEQIP, the IQC Summer URA, the NSERC Postdoctoral Fellowships Program and CryptoWorks21.